2016
DOI: 10.1186/s40463-016-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat and moisture exchanger use reduces in-hospital complications following total laryngectomy: a case–control study

Abstract: BackgroundTotal laryngectomy (TL) is an appropriate oncologic operation for many patients with laryngeal cancer delivering excellent oncologic outcomes, however it remains beset with significant functional consequences. Following TL, the upper and lower airways are permanently disconnected, which causes unfiltered, cold air with reduced humidity to enter the tracheobronchial tree, resulting in mucus overproduction and an increase in the viscosity of the mucus. In response to this, Heat and moisture exchangers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Previous studies have reported similar rates of daily cassette change and a cost benefit to using HMEs over ETH. 19,20 In this report, few barriers were identified to immediate and consistent use of an HME, with the majority of patients initiating HME use on POD 1. HME cassettes continue to be used (in lieu of ETH) for postoperative pulmonary rehabilitation at our organization.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have reported similar rates of daily cassette change and a cost benefit to using HMEs over ETH. 19,20 In this report, few barriers were identified to immediate and consistent use of an HME, with the majority of patients initiating HME use on POD 1. HME cassettes continue to be used (in lieu of ETH) for postoperative pulmonary rehabilitation at our organization.…”
Section: Discussionmentioning
confidence: 80%
“…Only one other study has compared the effect of ETH and HMEs on MP, with findings consistent with this report: a 44% frequency of MP in ETH users and a significant reduction in MP for those who used HME cassettes. 19 Furthermore, although several randomized controlled trials demonstrate the efficacy of HME cassette use in total laryngectomees, 14,20,21 PS/QI outcomes are likely far more pragmatic. This study's PS/QI design contributes otherwise unavailable effectiveness data surrounding in-hospital HME use.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective [10] and three prospective studies [11][12][13] have found xerostomia-and mucositis-related benefits in HN RT patients who utilized warm-mist humidification, and studies of inpatient warm-mist humidification have shown decreases in airway inflammation [14], mucus plugging [15], and mucus clearance [16]. However, the humidifiers in these studies are large specialized medical devices that are not easily translatable to an outpatient clinical setting.…”
Section: Introductionmentioning
confidence: 96%
“…12,13 In practice, the HME has shown to contribute to an improvement in pulmonary functioning of patients by decreasing mucus accumulation, frequent daily coughing, irritation of the respiratory tract, and infection of the airways (especially in the cold winter months). 1,2,5,9,[14][15][16] In one study, an improvement in breathing was reported by 88% of laryngectomy patients. 11 A randomized controlled study (RCT) by Mérol et al showed fewer pulmonary complaints, significantly fewer sleeping disturbances, and a higher level of satisfaction among patients using the HME.…”
Section: Introductionmentioning
confidence: 99%
“…3 Results of previous studies showed that healthcare costs related to HME use were lower compared with external air humidification in the postoperative setting. 10,16,19 An earlier costeffectiveness analysis concluded the use of the HME to be cost-effective in Poland. In this analysis, the occurrence of pulmonary events was estimated based on a survey conducted by physicians, and QoL was sourced from a study using a time-series design.…”
Section: Introductionmentioning
confidence: 99%